Fresno County Bar Association Luncheon re: Media - Watkins, Howard::::::::: (1984)
head table: Lanny Larson (Fresno Bee), ?, Carol Corey (KSEE-24); Donald Fischbach standing at lectern The Fresno Hilton main ballroom